The Chaos and Stability of Firefly Algorithm Adjacent Individual - Wen Xin Yu; Jun Nian Wang; Yan Li; Zheng Heng Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this paper, in order to overcome the defect of the firefly algorithm, for example, the slow convergence rate, low accuracy and easily falling into the local optima in the global optimization search, we propose a dynamic population firefly algorithm based on chaos. The stability between the fireflies is proved, and the similar chaotic phenomenon in firefly algorithm can be simulated.